2002
DOI: 10.1038/416759a
|View full text |Cite
|
Sign up to set email alerts
|

SWAP-70 is a guanine-nucleotide-exchange factor that mediates signalling of membrane ruffling

Abstract: Phosphoinositide-3-OH kinase (PI(3)K), activated through growth factor stimulation, generates a lipid second messenger, phosphatidylinositol-3,4,5-trisphosphate (PtdIns(3,4,5)P3). PtdIns(3,4,5)P3 is instrumental in signalling pathways that trigger cell activation, cytoskeletal rearrangement, survival and other reactions. However, some targets of PtdIns(3,4,5)P3 are yet to be discovered. We demonstrate that SWAP-70, a unique signalling protein, specifically binds PtdIns(3,4,5)P3. On stimulation by growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
252
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 207 publications
(258 citation statements)
references
References 31 publications
5
252
0
1
Order By: Relevance
“…As phosphatidylinositol 3-kinase has been reported to regulate Rac1 activity through the several guanine nucleotide exchange factors, such as SWAP70 and P-REX2 downstream of Gab1 (53)(54)(55), and Vav and Tiam-1 are also known to mediate Rac1 activity involved in transformation (56, 57), we initially speculated that the implication of Crk in HGF-mediated Rac1 activation may be partial. However, the significant suppression of HGF-dependent activation of Rac1, cell motility, and scattering was shown in Crk knockdown cells, which may suggest the crucial role for Crk in HGF-evoked activation of Rac1 and following cell motility in human synovial sarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…As phosphatidylinositol 3-kinase has been reported to regulate Rac1 activity through the several guanine nucleotide exchange factors, such as SWAP70 and P-REX2 downstream of Gab1 (53)(54)(55), and Vav and Tiam-1 are also known to mediate Rac1 activity involved in transformation (56, 57), we initially speculated that the implication of Crk in HGF-mediated Rac1 activation may be partial. However, the significant suppression of HGF-dependent activation of Rac1, cell motility, and scattering was shown in Crk knockdown cells, which may suggest the crucial role for Crk in HGF-evoked activation of Rac1 and following cell motility in human synovial sarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that several GEFs activate Rac1 in response to EGF and PDGF signaling [13,[23][24][25]. To determine which exchange factors activate Rac1 downstream of VEGF, we first investigated the endogenous expression of candidate Rac1 GEFs in endothelial cells.…”
Section: Exchange Factor Vav2 Couples Vegf Signaling To Rac1mentioning
confidence: 99%
“…The inositol-polyphosphate 5-phosphatases (referred to as 5-phosphatases) are a large family of signal-modifying enzymes that hydrolyze the 5-phosphate from the inositol ring of both inositol phosphates, such as Ins(1,4,5)P 3 and Ins(1,3,4,5)P 4 , and/or PtdIns-derived messenger molecules, including PtdIns(4,5)P 2 , PtdIns(3,4,5)P 3 , and PtdIns(3,5)P 2 (9). Ten mammalian and four yeast homologs have been identified and characterized.…”
Section: Phosphatidylinositolmentioning
confidence: 99%